Influence of the n-paraffins addition on the efficiency of the depressant for diesel fuel with various compositions; Химия и химическая технология в XXI веке; Т. 2 - Orlova А. (Химия и химическая технология на иностранном языке (английский), 2021)
Заглавие с титульного экрана